Modification of existing water turbine system for application at local river - Ahmad Makhzan, Ahmad Kamal (2010)
This thesis is about doing analysis and investigations on river flow rate in Malaysian River which focusing at Sungai Pahang. Through this analysis and investigation could obtain the potential of running a Water Turbine System (WTS). The main problem statement is on location limitation to obtain peak flow rate of river to running water turbine systems which is depending on depth and width of the river and also from the velocity of sectional area of river. Other than that, choosing most suitable water turbine system is also one of main criteria to be taken in this research. Water Turbine are one of clean renewable energy sources which holding high percentage of energy resource provider among renewable energy. The analysis and investigation are constrained from data of river volume flow rate which shows there are peaks values of volume flow rate in Pahang River. This thesis will carry on with modeling a WTS that can be recommended to construct in Pahang River. The analysis on flow rate of Pahang River are done by calculating potential Power (W) that could produced based on volume flow rate data that obtain from Department of Irrigation and Drainage of Malaysia. Since water turbine could provide electricity power without affecting pollution to the environment. Water turbines systems also are cheapest resource to be obtain. Final modeling of water turbine system is completed by using SolidWorks.